Culture and Imported Products: Extending Optimal Distinctiveness Theory with Acculturation - Nguyen Le; Sang Tan Huynh; Thanh Thi Bui; Quy Duy Do; Truong Xuan Nguyen (SAGE Open)
Cultural globalization has promoted consumer buying behavior toward imported products, especially in Asian countries. By extending optimal distinctiveness theory and acculturation theory, the authors aim to investigate the impact of the need for distinctiveness (NFD), acculturation to global consumer culture (AGCC), and brand reputation (BR) on consumer purchase behavior toward imported products (PB). This study applies the convenient random sampling method with a sample size of 764 Vietnamese consumers. A quantitative research method is applied, and structural equation modeling is analyzed using SmartPLS Software. The results show that NFD partially mediate the impact of AGCC on PB, which is crucial in exploring consumer behavior. Moreover, this study reveals that BR significantly moderates the relationship between AGCC, NFD and PB, proving the novel angle of BR in exploring PB. Then, the managerial implications will be proposed, providing marketing strategies to the managers of companies in the import industry to promote PB.